2007
DOI: 10.4161/cbt.6.5.4004
|View full text |Cite
|
Sign up to set email alerts
|

A phase I clinical trial of an adenovirus-mediated endostatin gene (E10A) in patients with solid tumors

Abstract: Purpose. The purpose of the current study were to assess the safety and feasibility of repetitive intratumoral administration of E10A, an adenoviral vector encoding the wild-type endostatin gene, to patients with solid tumors, and to evaluate its biologic effect and the pharmacokinetics of endostatin.Methods. Patients were treated with escalating doses from 1 × 10 10 VP to 1 × 10 12 VP of E10A intratumorally on days 1 and 8. Patients were assessed for toxicity and viral shedding, and antitumor response was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 21 publications
1
26
0
1
Order By: Relevance
“…Although recombinant endostatin is well tolerated, it has a short half-life and repeated dosing is required to achieve antitumor effects (Folkman, 2006). The therapeutic efficacy of an adenoviral expression vector (E10A) engineered to express high levels of endostatin in transduced cells has been tested in HNSCC patients (Lin et al, 2007;Li et al, 2008). Fifteen patients with solid tumors, including 2 patients with HNSCC, were treated with intratumoral injections of up to 10 12 viral particles on days 1 and 8 (Lin et al, 2007).…”
Section: Gene Augmentation Therapymentioning
confidence: 99%
“…Although recombinant endostatin is well tolerated, it has a short half-life and repeated dosing is required to achieve antitumor effects (Folkman, 2006). The therapeutic efficacy of an adenoviral expression vector (E10A) engineered to express high levels of endostatin in transduced cells has been tested in HNSCC patients (Lin et al, 2007;Li et al, 2008). Fifteen patients with solid tumors, including 2 patients with HNSCC, were treated with intratumoral injections of up to 10 12 viral particles on days 1 and 8 (Lin et al, 2007).…”
Section: Gene Augmentation Therapymentioning
confidence: 99%
“…Endostatin is a potent inhibitor of angiogenesis and has been safely used in replication-deficient Ad vector (Ad-Endo) in clinical trials for patients with advanced solid tumors. These Ad-Endo trials resulted in one objective response in a patient with nasopharyngeal carcinoma, 12 patients had stable disease, and two had disease progression [24] [25]. Ad-Endo has been used in combination with an Onc.Ad to amplify the endostatin expression in murine xenograft models, and this combination demonstrated more potent anti-tumor and antiangiogenic effects than treatments of either agent alone [26].…”
Section: Physical Barriers To Oncolytic Adenovirus Dissemination Withmentioning
confidence: 99%
“…A phase I clinical trial of E10A gene therapy has already been completed and the safety of this gene therapy has been confirmed. 29 Further, this preclinical study of the combined therapy employing showed no serious general toxicity or specific toxicity evident via histopathological analysis of key organ tissues (Figure 6b) in this mouse model. These findings are encouraging for the clinical application of this combined therapy.…”
Section: E10a and Metronomic Cisplatin For Scc Tumor Z Adhim Et Almentioning
confidence: 99%
“…Endostatin gene therapy using E10A, a replication-deficient recombinant adenovirus containing a wild-type of the human endostatin gene, could directly express the highly bioactive protein in vivo by means of the eukaryotic expression system, and post-translational modification and longterm storage could overcome the need for the cumbersome daily administration of endostatin protein. 29 The antiangiogenic effect of endostatin gene therapy with E10A, and the direct and indirect antitumor activity of metronomic low-dose cisplatin, offer an additive effect for tumor suppression. In this study, we combined intratumoral injections of E10A and intra-peritoneal injections of weekly low-dose cisplatin, and compared the antitumor and antiangiogenic effects of this combined therapy to several single-agent treatments in the H891.…”
Section: E10a and Metronomic Cisplatin For Scc Tumor Z Adhim Et Almentioning
confidence: 99%